Activism with the Nordic “brothers”: Cautious revival after years of decline? - Olesen, Mikkel Runge (Politica, 2017)
Danish activism in a Nordic context has suffered many setbacks since the end of the cold war. A central supplement strategy to the dominant Danish foreign and security policy in NATO during the cold war, Danish Nordic activism has since lost ground within the military sphere, the diplomatic sphere and the economic sphere. However, recent developments indicate that Danish Nordic activism may now experience a cautious revival, brought about by success with pragmatically focused cooperative projects for example in NORDEFCO and by the diffusion of Nordic ideals to a broader group such as Nordic Plus or within the EU. The NATO and EU divide between the Nordic countries, however, as well as differing national priorities in many different policy areas, still constitute considerable obstacles.